Transport studies Of NH4NO3 doped methyl cellulose electrolyte - Majid, Siti Rohana; Arof, Abdul Kariem; Shuhaimi, N.E.A.; Teo, L.P. (Elsevier, 2010)
This work reports on the transport properties of NH4NO3 doped methyl cellulose (MC) polymer electrolyte. The polymer electrolyte films were prepared by the technique of solvent casting. The highest room temperature conductivity of MC doped with 25 wt.% NH4NO3 is 2.10 +/- 0.37 x 10(-6) S cm(-1). Conductivity-temperature relationship obeys the Vogel-Tamman-Fulcher (VTF) rule from which the glass transition temperature, T-g was evaluated. The mobility, p and number density of charge carrier, n were calculated using the Rice and Roth model. (C) 2010 Elsevier B.V. All rights reserved.